Fancy nancy and the sensational babysitter eaudiobook - O'Connor, Jane (Fancy Nancy., 2012)
Nancy is so excited to meet her new sitter—especially because Alex is a high school student! She can't wait to play with dolls, play dressup, and have a fancy tea party. But when Alex shows up, Nancy is stunned. Her brand-new babysitter is . . . a boy!